Industrial policy and Foreign Direct Investment - Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2021)
Foreign Direct Investment (FDI) can benefit host countries by facilitating access to sophisticated technologies, good management and global value chains. However, multinational firms have many alternative locations from which to choose. As a consequence, countries trying to attract inflows of FDI need to consider what types of industrial policies will increase the country's attractiveness to foreign firms. Moreover, different types of FDI are of different value for the host country and might require different sets of policies. This paper starts by examining and discussing the global evolution of FDI. It continues by examining determinants to FDI and the types of industrial policies that are effective in attracting FDI. It ends with a discussion on quality FDI and how host country governments can maximize the benefits of FDI.
Keywords: F21; F23; F60; 330; FDI; MNE; Industrial policy; Host country effects